ANALISA MANAJEMEN RISIKO PADA PROYEK PDAM SEMARANG (STUDI KASUS: PROYEK PEMIPAAN IPA KALIGARANG SEMARANG BARAT) - Evy Agustina Purba; Monica Ade Kurnia B.; Jati Utomo Dwi Hatmoko; Frida Kistiani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Every construction project especially for PDAM project which responsible for water distribution has some risk that affect the construction. One of the common problems which became risk for the PDAM project is the pipe leakage level. The average of indonesia’s pipe leakage level is more than 30%. This research is about risk management of IPA Kaligarang piping project analyzing based on Work Breakdown Structure (WBS). The aim of this research is to identify, analyze, evaluate and manage the existing risk of IPA kaligarang piping project. The matter of this research is limited for the construction phase. IPA Kaligarang Piping project is a project of West Semarang PDAM. Based on identification and risk assessment, IPA Kaligarang West Semarang PDAM piping project had 23 risks which is found almost at each Work Breakdown Strukture(WBS) project. For then more through analyzing and evoluation process, the result of this research is the risks of PDAM projects consist of two categories. The categories are moderate risk which has 14 work items (39%) and low risk which has 74 work items (61%). The whole 23 risks that found can be managed, like permitting risk can be managed by asking government approval, The risk of workers excalation or reduction can be managed by making the barchart of workers or reschedule, etc. The contractor is the one who responsible of the whole risk, and there’s no high risk that will obstruct the construction of IPA Kaligarang West Semarang piping project.